2022
DOI: 10.1002/ange.202201870
|View full text |Cite
|
Sign up to set email alerts
|

A Desaturative Approach for Aromatic Aldehyde Synthesis via Synergistic Enamine, Photoredox and Cobalt Triple Catalysis

Abstract: Aromatic aldehydes are fundamental intermediates that are widely utilised for the synthesis of important materials across the broad spectrum of chemical industries. Accessing highly substituted derivatives can often be difficult as their functionalizations are generally performed via electrophilic aromatic substitution, SEAr. Here we provide an alternative and mechanistically distinct approach whereby aromatic aldehydes are assembled from saturated precursors via a desaturative process. This novel strategy har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
0
0
0
Order By: Relevance
“…In addition, Leonori's group found that a synergistic combination of morpholine, photoredox conditions and Co catalysis could transform saturated cyclohexane formaldehyde into an aromatic aldehyde through the same Co-regulated radical mechanism (Scheme 45f). 373 Very recently, Zuo's group demonstrated Co/bisphosphonium-catalyzed the selective C(sp 3 )−H dehydrogenation of benzylic alcohols (45-34) (Scheme 45g). 374 The photocatalytic system demonstrated high efficiency when applied in continuous-flow conditions, even using a straightforward and readily assembled continuous-flow setup.…”
Section: Hat Between Radicals and Co Complexesmentioning
confidence: 99%
“…In addition, Leonori's group found that a synergistic combination of morpholine, photoredox conditions and Co catalysis could transform saturated cyclohexane formaldehyde into an aromatic aldehyde through the same Co-regulated radical mechanism (Scheme 45f). 373 Very recently, Zuo's group demonstrated Co/bisphosphonium-catalyzed the selective C(sp 3 )−H dehydrogenation of benzylic alcohols (45-34) (Scheme 45g). 374 The photocatalytic system demonstrated high efficiency when applied in continuous-flow conditions, even using a straightforward and readily assembled continuous-flow setup.…”
Section: Hat Between Radicals and Co Complexesmentioning
confidence: 99%
“…4,5 The renewed interest in this catalytic methodology is owed to the mild reaction conditions employed, the robust functional group tolerance, and the possibility to access redox-neutral reaction routes unattainable with classical ionic chemistry triggered by thermal activation. 6,7 Besides, the use of visible light is seen as an ideal driving force for catalytic transformations, [8][9][10][11][12][13][14] in order to establish a greener chemical industry within the forthcoming decarbonization of our economy. 15 Despite the novelty of the approach, the method relies on the use of Ir or Ru-containing photocatalysts (chiefly, Ir[dF(CF3)ppy]2(dtbbpy)PF6 or Ru[dF(CF3)ppy]2(dtbbpy)PF6, where (dF(CF3)ppy = 2-(2,4difluorophenyl)-5-(trifluoromethyl)pyridine, and dtbbpy = 4,4′-di-tert-butyl-2,2'-bipyridine)), homogeneous Ni co-catalysts, and additional bipyridyl compounds for ligating the Ni centers, as summarized in Fig.…”
Section: Main Textmentioning
confidence: 99%